Jogo de papéis à luz da teoria histórico-cultural: pressupostos teóricos-metodológicos para a educação infantil - Bertolo, Sara Manzini (2022)
This theoretical research is the result of a theoretical-bibliographic study about the role-playing activities in the Early Childhood Education based on the Historical-Cultural Theory. As guiding thread of our investigation we elaborate the following question: What are the theoretical-methodological foundations required for the Early Childhood teacher to develop and evaluate the role-playing activity based on the Historical-Cultural Theory with children from three to five years old? In order to answer the question, we elucidate the objective: to systematize the theoretical-methodological foundations needed to understand the process of development and evaluation of the role-playing activity in Early Childhood Education, from the perspective of Historical-Cultural Theory, for the Education teacher Children work with children from three to five years old. The methodological course followed the historical-dialectical materialism and Vygotsky's genetic method by reading books of classical authors and researchers who study the subject. The data collection and analysis procedure was supported by the methods and techniques of bibliographic research proposed by Salvador. We chose as a category of analysis the theoretical-methodological foundations, procedures and instruments of the researches on role-playing with children in Early Childhood Education based on the Historical-Cultural Theory. The fundamental elements of the role-playing activity are content, objects, ludic actions and authentic relationships. The investigations show that the systematization of this activity comprises the planning, execution and evaluation of the teacher, for this reason, it is necessary for her to identify or suggest the content of the role game; elect and delimit the characters of the game; to choose and delimit the objects of the game and their dispositions in the school space; identify the game's ludic actions; identify and develop authentic relationships in the game. Thus, the research shows specificities for the instruments' applications and theoretical-methodological procedures to the game's elements, such as conversation circles, problem-solving through questions, presentation and/or creation of objects, videos, figures and so on. We conclude, therefore, that the implications of this research for pedagogical practices converges in the improvement of theorical-methodological strategies for teachers to develop and apply in the game activity in order to enhance the cultural development of children.